DOI: HTTPS://DOI.ORG/10.36873/AE , ALPIAN, YANCILUK, DAN WAHYU SUPRIYATI : PEMBUATAN PELET DARI SERBUK LIMBAH KAYU MENGGUNAKAN ALAT PENGEMPA DAN CETAK SEDERHANA - Agrienvi (Agrienvi, Jurnal Ilmu Pertanian, 2019)
ABSTRACTEnergy demand increase follow to population growth factors, high exploration costs, rising world oil prices andthe difficulty of finding sources of oil reserves. These factors cause the governments of several countries to immediatelyproduce alternative energy that is renewable and environmentally friendly. Wood pellets are an alternative energysource. The availability of raw materials is very easy to obtain. Raw materials for wood pellets from the exploitationwaste such as logging residues, branches and twigs, wood industry waste such as scraps, sawdust and bark,agricultural waste such as straw and husks. Waste that is developed into a product will produce a higher economicvalue. Making pellets from wood waste is an alternative energy material for meeting people's energy needs. Theopportunity to develop wood pellets as fuel is wide open because of the vast potential of forests in Indonesia and thelarge amount of waste from forest products, both from timber industry waste and exploitation waste. Equipment, rawmaterials and the process of making pellets in a simple manner need to be socialized to the public so that they can beapplied especially for the utilization of potential waste that can be used as raw material for making pellets.Keywords : wood pellets, waste, simple technology, renewable energy